2011
DOI: 10.1111/j.1365-2621.2011.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Are consumer profiling techniques equivalent for some product categories? The case of orange‐flavoured powdered drinks

Abstract: Taking into account consumers' perception in new product development has been regarded as a key strategy to developing more successful food products. In this context, consumer profiling techniques have increased their popularity in the last decade. The aim of the present work was to compare four consumer profiling techniques (sorting, projective mapping, intensity scales and check-all-that-apply questions) in orangeflavoured powdered juice drinks. A consumer study was carried out with 200 regular consumers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 13 publications
2
48
0
4
Order By: Relevance
“…It is interesting to highlight that although CATA questions do allow a direct measurement of the intensity of sensory attributes, the percentage of consumers who selected a term provided similar information to average intensity scores regarding similarities and differences among samples. Similar results have been reported by Ares, Varela, Rado, and Giménez (2011b) and Parente, Ares, and Manzoni (2011).…”
Section: Discussionsupporting
confidence: 94%
“…It is interesting to highlight that although CATA questions do allow a direct measurement of the intensity of sensory attributes, the percentage of consumers who selected a term provided similar information to average intensity scores regarding similarities and differences among samples. Similar results have been reported by Ares, Varela, Rado, and Giménez (2011b) and Parente, Ares, and Manzoni (2011).…”
Section: Discussionsupporting
confidence: 94%
“…The interest of using Napping Ò to map the perception of packages, claims and labels, in comparison with other descriptive or evaluative methods, lies in its being an intuitive, less rational method for consumers to use (Ares, Varela, Rado, & Giménez, 2011). Due to its holistic nature, consumers think of the package as a whole rather than about particular individual attributes, which is closer to what happens in front of the supermarket shelf.…”
Section: Introductionmentioning
confidence: 97%
“…Organoleptic properties of flavoured fermented camel milk treatments Consumer acceptance of healthy food products is strongly dependent on the sensory characteristics of these products (Ares, 2011). The organoleptic properties of the prepared fermented milk as shown in Table ( 9) showed that increasing levels of cinnamon and doum extracts negatively influenced the sensory scores of some properties of fermented camel milk The maximum attainable score was given for appearance of all fresh samples, whereas after 21 days of storage the samples flavoured with the highest amount of cinnamon and doum extracts ranked the lowest score for appearance.…”
Section: Microbiological Properties Of Flavoured Fermented Camel Milkmentioning
confidence: 99%